Fandom, Second Edition : Identities and Communities in a Mediated World - Harrington, C. Lee, 1964-; Sandvoss, Cornel; Gray, Jonathan (Jonathan Alan) (Book collections on Project MUSE., 2017)
We are all fans. Whether we follow our favorite celebrities on Twitter, attend fan conventions such as Comic Con, or simply wait with bated breath for the next episode of our favorite television drama--each of us is a fan. Recognizing that fandom is not unusual, but rather a universal subculture, the contributions in this book demonstrate that understanding fans--whether of toys, TV shows, celebrities, comics, music, film, or politicians--is vital to an understanding of media use, audiences, engagement, and participatory culture in a digital age. Including eighteen new, original essays covering topics such as activism directed at racism in sports fandom, fan/producer interactions at Comic Con, the impact of new technologies on fandom, and the politics and legality of fanfic, this wide-ranging collection provides diverse approaches to fandom for anyone seeking to understand modern life in our increasingly mediated, globalized, and binge-watching world. -- Back cover.